simplifique:
(+10)+(-4) =
(-8)+(+6)=
(+3)+(-7)+(-1)=
(-12)+(+8)+(-5)+(-2)
Soluções para a tarefa
Respondido por
1
(+10)+(-4) = 10-4 = + 6
(-8)+(+6)= - 8 + 6 = - 2
(+3)+(-7)+(-1)= 3 - 7 - 1 = - 5
(-12)+(+8)+(-5)+(-2)= - 12 + 8 - 5 - 2 = - 11
Respondido por
1
( + 10 + ( -4)
+ 6
( - 8) + (+6)
- 2
( + 3) + ( -7) + ( - 1)
- 4 - 1
- 5
( + 3) + ( - 7) + ( - 1)
- 4 - 1
- 5
( - 12) + ( + 8 ) + ( - 5) + ( -2)
- 4 - 5 - 2
- 11
+ 6
( - 8) + (+6)
- 2
( + 3) + ( -7) + ( - 1)
- 4 - 1
- 5
( + 3) + ( - 7) + ( - 1)
- 4 - 1
- 5
( - 12) + ( + 8 ) + ( - 5) + ( -2)
- 4 - 5 - 2
- 11
Perguntas interessantes
Artes,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás